Faktor-Faktor yang Memengaruhi Keterpilihan Perempuan di Dewan Pewakilan Rakyat Daerah Kota Medan pada Pemilu 2019 - Sri Rahayu; Arif Nasution; Arifin Saleh (Universitas Medan Area, 2021)
The electability of women as Members of the Medan City DPRD in the 2019 Election is still not as expected, namely only reaching 12% of the minimum 30% stipulated by law. This study aims to determine what factors influence the electability of women in the Electoral District 3 DPRD Medan City in the 2019 Election. This research uses quantitative methods. The method of determining the sample using the Slovin formula. The sampling method used was proportional stratification random technique (startified proportional random sampling), obtained 100 samples from 192,315 populations. The data collection method is done by distributing questionnaires to respondents. The data analysis method used multiple linear regression using SPSS 25 software. The results showed that the variables of gender, ethnicity and physical appearance had a significant effect on women's electability in the election area 3 DPRD Medan City. Based on the results of multiple linear regression analysis tests and partial tests, the physical appearance variable (physival appearance) became the dominant factor in increasing the electability of women compared to the gender (gender) and ethnicity (ethnicity) variables which were 0.622.